ChemInform Abstract: Hexagonal Ferrites of X‐, W‐, and M‐Type in the System Sr—Fe—O: A Comparative Study. Issue 27 (18th June 2015) - Toepfer, Joerg; Seifert, Daniela; Le Breton, Jean‐Marie; Langenhorst, Falko; Chlan, Vojtech; Kouril, Karel; Stepankova, Helena
Abstract While investigating the Fe‐rich part of the pseudo‐binary system SrO—Fe2O3, the well‐known M‐type SrFe12O19 (I) and two additional ferrites, W‐type SrFeII2FeIII16O27 (II) and X‐type Sr2FeII2FeIII28 O46 (III) are found at high temperatures from calcined and sintered mixtures of SrCO3 and Fe2O3 (1200 °C for (I); 1370 °C for (III); 1400 °C for (II), all 24 h).